SAT0363 Validation of the Ankylosing Spondylitis Disease Activity SCORE (ASDAS) and Effectiveness of Infliximab in the Treatment of Ankylosing Spondylitis over 4 Years. (10th June 2014) - Rahman, P.; Choquette, D.; Khraishi, M.; Bensen, W.; Shaikh, S.; Sholter, D.; Sheriff, M.; Rampakakis, E.; Sampalis, J.S.; Nantel, F.; Otawa, S.; Lehman, A.; et al.
Abstract : Objectives: To assess in a clinical practice the 4-year outcomes in patients with AS treated with infliximab and the performance of ASDAS, a new disease activity measure in AS. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with infliximab or golimumab as first biologics or after having been treated with a biologic for less than 6 mos. AS patients treated with infliximab between 2005 and 2012 were included. Descriptive statistics were produced for clinical outcome measures and patient reported outcomes at baseline and follow-up assessments over four years. Within-group changes were assessed for statistical significance with the paired-samples Student's t-test. The correlation of ASDAS with BASDAI and BASFI was assessed with the Pearson correlation coefficient. The correlation of these measures with MDGA was assessed with the Spearman's rho. Results: A total of 230 AS patients who had at least one follow-up assessment were included in this analysis, with a mean (SD) age of 45.7 (11.5) years and mean (SD) disease duration since diagnosis of 10.0 (10.1) years. At the time of enrollment, mean (SD) patient parameters were: C-reactive protein (CRP) =16.9 (20.2) mg/dL, erythrocyte sedimentation rate (ESR) =25.8 (20.2) mm/hr, morning stiffness =74.6 (40.2), health assessment questionnaire (HAQ-DI) =1.20 (0.61), physician global assessment of disease activity (MDGA) =6.6 (1.9), BASDAI =6.4 (2.1), BASFI =6.1 (2.5), and ASDAS =3.8 (1.0). By 6 mos of treatment significant improvements (P<0.01) were observed in all clinical and patient outcome parameters studied, which were sustained or further enhanced over 48 months of treatment. Similar significant changes were observed in ASDAS, BASDAI, and BASFI over time providing evidence of construct validity and sensitivity to change. A strong positive linear correlation between ASDAS and BASDAI (r=0.85; P<0.001) and BASFI (r=0.76; P<0.001) was observed. The correlation of MDGA was strong with ASDAS (rho=0.73; P<0.001) and BASDAI (rho=0.70; P<0.001) and moderate with BASFI (rho=0.64; P<0.001). The proportion of patients with very high disease activity (ASDAS >3.5) decreased from 62.4% at baseline to 6.9% at 48 months. Conclusions: Treatment with infliximab over four years is effective in reducing symptom severity and improving outcomes in patients with AS. Furthermore, the data from this registry confirm the validity and sensitivity to change of the ASDAS score in a real-world AS cohort. Disclosure of Interest: P. Rahman: None declared, D. Choquette: None declared, M. Khraishi: None declared, W. Bensen: None declared, S. Shaikh: None declared, D. Sholter: None declared, M. Sheriff: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, F. Nantel Employee of: Janssen, S. Otawa Employee of: Janssen, A. Lehman Employee of: Janssen, M. Shawi Employee of: Janssen DOI: 10.1136/annrheumdis-2014-eular.2381